Zygotorulaspora dagestanica sp. nov., a novel ascomycetous yeast species associated with the Georgian honeysuckle (Lonicera iberica M. Bieb.). Issue 4 (26th April 2021) - Kachalkin, Aleksey V.; Abdullabekova, Dinakhanum A.; Magomedova, Elena S.; Yurkov, Andrey M.
Abstract : During an investigation of the yeast communities associated with wild fruit shrubs in Dagestan (Caucasus, Russia), four fermenting ascospore-producing yeast strains were isolated from leaves of the Georgian honeysuckle ( Lonicera iberica M. Bieb.) and from soil underneath this plant. Phylogenetic analyses based on concatenated sequences of the ITS region and D1/D2 domains of the large subunit rRNA gene and concatenated sequences of the ribosomal DNA cystron, RPB2 and TEF1 genes showed that the isolated strains represented a new species of the genus Zygotorulaspora . The new species was placed in the basal position to other species of the clade and close to Zygotorulaspora mrakii . Based on the results of phylogenetic analyses and the phenotypic characteristics of the four studied strains, a novel species is described, for which the name Zygotorulaspora dagestanica sp. nov. is proposed. The holotype is KBP Y-4591 T, three metabolically inactive cryopreserved isotype cultures are DSM 100088, VKM Y-3060 and VKPM Y-4318. The MycoBank number is MB 838285.